Pengaruh Kualitas Produk, Harga dan Lokasi terhadap Keputusan Pembelian Kerang Hijau (Perna viridis L.) - Nur Safitri; Siti Wahana; Andung Rokhmat Hudaya (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Aim of this research are 1) Does product quality, price and location simultaneously influence green mussel purchasing decisions. 2) Does product quality, price and location partially influence the buying decision of green mussels. The research design used is descriptive quantitative research using survey techniques. The population used is green mussel consumers who are in Gunung Jati District, Cirebon Regency. The part that was studied was the effect of product quality, price and location on green mussel purchasing decisions. The number of samples used was 75 respondents with a non-probability sampling technique using accidental sampling. The data analysis technique used multiple linear regression tests. The results of the study show that 1) Partially or individually, product quality does not significantly influence green mussel purchasing decisions. 2) Partially or individually, the price variable and location variable have a significant effect on the purchasing decision of green mussels. 3) Simultaneously or together that the product quality variables, price variables and location variables have a significant effect on green mussel purchasing decisions in Gunung Jati District, Cirebon Regency.